Analysis of Vehicle Identification Markings: Validation of Methodologies for Forensic Purposes - E. V. Chesnokova (Теория и практика судебной экспертизы, 2018)
The article discusses the question of assessing the forensic validity of methodologies for the analysis of vehicle identification markings. The need is emphasized for further piecemeal efforts to achieve the goals of standardization of forensic science practices.